Distribution and diffusion of surface suspended matter off the East China Shore, 2010. (9th June 2016) - Liu, Xue; Li, Guangxue; Ma, Yanyan; Ding, Dong; Dada, Olusegun A.; Xu, Jishang; Qiao, Lulu; Li, Jianchao; Liu, Shidong
Abstract: It is a question whether the suspended sediment from the China continent could enter the Kuroshio Current and Pacific Ocean. Surface suspended matter (SSM) and sea surface temperature (SST) in the East China Seas from December 2009 to November 2010 has been extracted from the satellite NOAA‐19 AVHRR/3. We have monitored the change of the SSM diffusion during summer half‐year and winter half‐year. High SSM areas occur in the inshore of the Liaodong Bay, Bohai Bay, Yellow River Delta, Shandong Peninsula, Jiangsu Coast and Yangtze Estuary, especially blooming in winter half‐year. Going by our findings, the sediment provenance influences the SSM distribution, and the current system and monsoon are important factors that drive the SSM diffusion all year round. In winter half‐year, the ocean colour images show that the current system is well developed. The SSMs are transported southeastward, and a part reaching the outer continental shelf is captured by the Kuroshio Current before it finally reaches the open Pacific Ocean through the Tokara Strait. Some SSMs are transported by the Yellow Sea and Tsushima Warm Current into the Yellow Sea and Japan Sea. In summer half‐year, most of the SSM could not reach the continental shelf break and only little SSM could be captured by the Kuroshio Current into the open ocean. Copyright © 2016 John Wiley & Sons, Ltd.